2021
DOI: 10.1038/s41437-021-00459-0
|View full text |Cite
|
Sign up to set email alerts
|

Combining conventional QTL analysis and whole-exome capture-based bulk-segregant analysis provides new genetic insights into tuber sprout elongation and dormancy release in a diploid potato population

Abstract: Tuber dormancy and sprouting are commercially important potato traits as long-term tuber storage is necessary to ensure year-round availability. Premature dormancy release and sprout growth in tubers during storage can result in a significant deterioration in product quality. In addition, the main chemical sprout suppressant chlorpropham has been withdrawn in Europe, necessitating alternative approaches for controlling sprouting. Breeding potato cultivars with longer dormancy and slower sprout growth is a desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Due to the very poor resolution of the genetic map in the previous studies, except by Sharma et al ( 2021 ), and largely the deployment of non-sequence-tagged markers, detailed comparisons with the current study are not possible, however, many QTL reported here appear to be in approximately the same genomic locations as reported previously including the detection of novel QTL regions (Table 5 ). A much more recent study (Sharma et al 2021 ) conducted with high map resolution reports tuber dormancy/sprouting QTL on chromosomes 1–8 and 10. Of these, chromosomes 8 and 10 QTL were not detected in the current study but all other QTL (i.e.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Due to the very poor resolution of the genetic map in the previous studies, except by Sharma et al ( 2021 ), and largely the deployment of non-sequence-tagged markers, detailed comparisons with the current study are not possible, however, many QTL reported here appear to be in approximately the same genomic locations as reported previously including the detection of novel QTL regions (Table 5 ). A much more recent study (Sharma et al 2021 ) conducted with high map resolution reports tuber dormancy/sprouting QTL on chromosomes 1–8 and 10. Of these, chromosomes 8 and 10 QTL were not detected in the current study but all other QTL (i.e.…”
Section: Discussionmentioning
confidence: 59%
“…on chromosomes 1–7) find higher correspondence with the GWAS QTL-MTAs reported here. None of the previous studies report QTL for this trait on chromosome 12 except Sharma et al ( 2021 ) who suggest the presence of an effective QTL peak at the bottom end of this chromosome but the required statistical significance in their study was not achieved. The chromosome 12 QTL–MTA (Table 5 ) observed here strongly overlaps, and further strengthens, the chromosome 12 candidate QTL suggested by Sharma et al ( 2021 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It was inferred that this mutation leads to the retention of the second intron and premature termination of the HvCSLC1 protein (Gajek et al, 2021). The combined bulk segregant analysis and whole exomecapturing methods employed in potatoes for studying tuber sprout elongation corroborated different QTL sites, helped to narrow down the related genomic regions, and discovered novel QTLs (Sharma et al, 2021). Overall, with this focused strategy, crop development efforts are more precisely made while simultaneously speeding up the breeding process.…”
Section: Exome Sequencing Applications In Crop Improvementmentioning
confidence: 99%